2018
DOI: 10.1039/c8cc02777c
|View full text |Cite
|
Sign up to set email alerts
|

Proton triggered circularly polarized luminescence in orthogonal- and co-assemblies of chiral gelators with achiral perylene bisimide

Abstract: The orthogonal- or co-assembly of achiral perylene bisimide (PBI) with chiral gelators can be regulated by solvents. While the coassembly leads to the formation of chiroptical nanofibers through chirality transfer, the orthogonal assemblies could not. Moreover, protonation on the coassembled nanofibers could light up the circularly polarized luminescence (CPL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 58 publications
0
47
0
Order By: Relevance
“…However, the CPL properties of obtained chiral materials are some-times unpredictable, and a tedious synthesis process is always inevitable [23,24]. In this context, the combination of chiral host with achiral luminescent guests through chirality transfer to fabricate CPL-active materials recently becomes an arising approach [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CPL properties of obtained chiral materials are some-times unpredictable, and a tedious synthesis process is always inevitable [23,24]. In this context, the combination of chiral host with achiral luminescent guests through chirality transfer to fabricate CPL-active materials recently becomes an arising approach [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the chiral template molecules still require elaborate design and tedious synthesis in the system, developing a simple and versatile chiral host matrix without tedious synthesis should be one of the most important issues in this research field. In addition, most of the reported cases involve a solution phase which definitely limited the practical applications [30,31]. It is emergent to develop solid-state CPL-active materials by a general approach.…”
Section: Introductionmentioning
confidence: 99%
“…The tertiary amine group is a strong electron donor and can be easily protonated [33]. In our previous research, it was found that morphologies and properties of aggregates can be significantly influenced by hydrochloric acid and the molecular structure of PBI with tertiary amine groups.…”
Section: Introductionmentioning
confidence: 99%
“…However,during the formation of higher-order hierarchical assemblies,t heir supramolecular chirality could be either switched or transformed. [4] However,among the reported examples helicity and ground-state chirality switching have been the main focuses, [5,6] and the inversion and switching of the excited-state chirality and circularly polarized luminescence (CPL) has been rarely studied. [2] In another case, although the constituent molecules of luciferin, acting as emitters,h ave the same molecular chirality,t hey emit circularly polarized light of opposite sense when incorporated into macroscopic mirror-image structures.…”
mentioning
confidence: 99%
“…[3] Both of these different structural and functional characteristics essentially result from their supramolecular chirality rather than the intrinsic molecular chirality.I nspired by the fascinating natural phenomena, the exploration of supramolecular systems featuring chirality switching,i np articularly inversion, from enantiomeric pure building blocks has attracted great attention recently. [4] However,among the reported examples helicity and ground-state chirality switching have been the main focuses, [5,6] and the inversion and switching of the excited-state chirality and circularly polarized luminescence (CPL) has been rarely studied. [7] Coordination and p-p stacking are widely applied in supramolecular assemblies because of their unique directionality and stacking modes.…”
mentioning
confidence: 99%